Gender and informal urban sanitation : experiences and management of shared sanitation in Phomolong Informal Settlement in Pretoria, South Africa - Thebe, Vusilizwe (University of Pretoria, 2020)
Dissertation (MSocSci)--University of Pretoria, 2019.